A conceptual knowledge management system for managing knowledge of youth development programs within a collaborative environment - Abdullah, Rusli; Omar, Siti Zobidah; Mohamed Shaffril, Hayrol Azril (2016)
The Youth Development Program (YDP) is the concept on how the programs are developed and managed for the purpose of youth towards eco-friendly development system by members of community of practice (CoP) in sustaining the impact economically especially in related to the YDP knowledge (tacit and explicit) called 5 Kx’s Model which consist of knowledge collection (KC), knowledge transfer (KT), Knowledge Exchange (KE), Knowledge Utilization (KU), and Knowledge Recommendation (KR). In order to ensure this concept is working based on the user requirement and its program, there are many people who are working together collaboratively (synchronously and asynchronously) as the members of community to promote the lessons learnt and best practise knowledge. The CoP in YDP environment includes the youth administrator, youth agency, youth partner, and youth organizer as well as the youth individually. Based on this scenario of working collaboratively in order to promote knowledge sharing of YDP knowledge among the CoP, there is a need for a tool called conceptual knowledge management system (KMS-YDP) in managing and sharing the knowledge about YDP activities. The combination of these topics will be discussed based on the conceptual and its modelling on how the KMS can offer KM processes as well as its capabilities through knowledge life cycle which starts from knowledge acquisition, knowledge storing, knowledge dissemination, and knowledge application for the benefits of the CoP in YDP environment to work collaboratively. Therefore, by using the KMS-YDP model in managing knowledge of YDP, it can utilize the knowledge in sustaining the environment impact economically. Besides that, they can also deliver as a good platform to enhance the quality of service among the CoP.